Multiple Endodontic Guides for Root Canal Localization and Preparation in Furcation Perforations: A Report of Two Cases - Shaban, Amal; Elsewify, Tarek Medhat; Hassanein, Ehab E. (Iranian Endodontic Journal, 2023)
Perforations are managed by surgical or nonsurgical approach depending on the relationship of the perforation site to the crestal bone level and attachment apparatus. Relocating the canal orifice or root canal close to the perforation site is quite challenging even with the aid of a dental operating microscope. In these two case reports, guided endodontics was applied in root canal localization and preparation in cases of furcation perforations. This is the report of two patients (42 and 15-year-old, respectively) who were referred for root canal treatment of the mandibular right first molar. The first case complained of pain on biting, foul odor, and bad taste. The referring dentist noted a furcation perforation and an inability to locate the mesial canals. Radiographic examination showed furcation radiolucency. Definitive diagnosis was symptomatic apical periodontitis. The second case complained of severe throbbing pain along with pain on biting. Mesial canals could not be detected due to a furcation perforation as noted by the referring dentist. Radiographic examination revealed a large furcation perforation and related bone resorption. Definitive diagnosis was acute apical abscess. In each case, a silicone impression of the mandibular arch was obtained and scanned along with cone-beam computed tomography scan to plan for localization and preparation of the mesiobuccal canals using implant planning software. Multiple guides were fabricated through rapid prototyping and allowed for the correct orientation and insertion of endodontic files through the canal. Canals were prepared and then obturated using warm vertical compaction technique and the perforation were repaired by mineral trioxide aggregate (MTA). Six-month and one-year follow-ups revealed no symptoms and evidence of radiographic healing. Thus, multiple endodontic three-dimensional guides can be successful in root canal localization and preparation in cases of furcation perforations.